Transparent Yb3+ doped phosphate glass-ceramics. Issue 16 (November 2020) - Hongisto, M.; Veber, A.; Boetti, N.G.; Danto, S.; Jubera, V.; Petit, L.
Abstract: Yb 3+ doped oxyfluorophosphate glasses with the composition (98.75) [90NaPO3 -(10-x) Na2 O-xNaF] - 1.25Yb2 O3 (in mol%) with x = 0, 2.5, 5, 7.5 and 10 were prepared using a standard melting process. The progressive replacement of Na2 O by NaF leads to an increase in the number of Q 2 units at the expense of the Q 1 units. This increase in the polymerization of the glass network leads to a shift of the optical band gap to lower wavelength, to a slight increase in the intensity of the emission at 1000 nm and more importantly to a change in the glass crystallization process. Indeed, both surface and bulk crystallization were observed in the glass with x = 0 while surface crystallization only occurs when NaF is added in the phosphate network. The heat treatment leads to the precipitation of at least three crystalline phases: as x increases, the NaPO3 phase grows at the expense of Na5 P3 O10 . All glasses precipitate the Yb containing crystal, NaYbP2 O7 which leads to an increase in the intensity of the emission at 1000 nm compared to the emission at 975 nm. We show for the first time to the best of our knowledge that transparent Yb 3+ doped phosphate glass-ceramics can be obtained within this glass system when free of NaF.